Analisis Hukum Atas Akses Pendidikan Bagi Anak-Anak Migran Indonesia di Malaysia Berdasarkan Konvensi Hak Anak dan Hukum Malaysia - Anggraeni, Hari Sri; Tohari , Mohamad; Susilowati, Tri (Universitas Pahlawan Tuanku Tambusai, 2025)
This research aims to analyze access to education for Indonesian migrant children in Malaysia based on the Convention on the Rights of the Child (CRC) and Malaysian law. Indonesian migrant children in Malaysia face various barriers to obtaining quality education, despite education being a fundamental right guaranteed by international law. This study identifies relevant regulations and policies, as well as analyzes the implementation of educational principles in the CRC. Based on the review of the Education Act 1996, the Child Act 2001, and Malaysia's immigration policies, this research finds that while Malaysia has ratified the CRC, its implementation of the right to education for Indonesian migrant children is hindered by discriminatory policies, unclear citizenship status, and fears of deportation. This study also reveals that many Indonesian migrant children are forced to rely on informal, high-cost education, while access to formal schools is extremely limited. Therefore, this study recommends policy reforms that are more inclusive and human rights-based to improve the education of migrant children in Malaysia.